A study on 'Personal Data Protection Act 2010' in govenrning transborder data flow in Malaysia / Muhammad Zaidi Izman Murugan, Nik Mohd Izzat Nik Ahmad Azman and Mohamad Hafizzuddin Mohd Azmin - Izman Murugan, Muhammad Zaidi; Nik Ahmad Azman, Nik Mohd Izzat; Mohd Azmin, Mohamad Hafizzuddin (2012)
This research mainly focuses on the Personal Data Protection Act (PDPA) on how it works and how it is govern whether in national level or international level. The PDPA has been gazetted on the year Of 2010 but still not coming into forced. Here, the effectiveness of the PDPA will be fully analysed whereby all the pros and cons will be stated. The series of literature are reviewed as we compared the PDPA of Malaysia with other countries for example China, Republic of Korea, India and United States of America. From the literature review also look on the international instrument that governs the personal data for instances European Directive, for Economic Co-operation and Development (OECD), the Asia-Pacific Economic Cooperation (APEC) and many more. Besides the literature review also proof that the PDPA of Malaysia is still not perfect and need to be improved as all of us are concerned that the personal data transfer are happened everyday and every second in the world. This research hopes to assist the government to make a better PDPA and also to help people to understand the important of PDPA.